PROGRAM LITERASI KELUARGA DALAM UPAYA MENINGKATKAN PRESTASI BELAJAR ANAK DI SEKOLAH DASAR - Raiya Muhamad Febrian; Arif Fauzan; Ichsan Fauzi Rachman (CV. ADIBA AISHA AMIRA, 2025)
This research aims to evaluate the impact of family literacy programs on elementary school children's academic achievement. Using a quantitative research method with a literature review approach, data were analyzed from various sources such as books, scientific journals, and online resources. The results of the literature review indicate that literacy plays a crucial role in developing children's abilities in reading, writing, and critical thinking. Challenges in improving children's literacy in Indonesia include the influence of rapid technological and informational advancements. Family literacy programs are considered as one of the solutions to enhance children's literacy, with parents playing a significant role in providing literacy stimulation from an early age. Program evaluation is conducted through rewards and sanctions, as well as through a nurturing and wise educational approach. These findings provide a deeper understanding of the importance of family literacy in supporting children's academic achievement in elementary school.